PENGARUH PEMBERIAN EKSTRAK ETANOL DAUN KASTURI (Mangifera casturi kosterm) TERHADAP PENURUNAN KADAR HIPERLIPIDEMIA PADA MENCIT PUTIH (Mus musculus): THE EFFECT OF ADMINISTERING ETHANOL EXTRACT OF MANGIFERA CASTURI (Mangifera casturi kosterm) LEAVES ON REDUCING HYPERLIPIDEMIA LEVELS IN WHITE MICE (Mus musculus) - Tyananda Sahara; Anita Ratna Dilla; Nur Mahdi (DSM Publisher, 2026)
Hyperlipidemia is a condition characterized by increased lipid levels in the blood, which is a major risk factor for cardiovascular diseases and strokes. Therefore, an alternative treatment therapy using natural ingredients is needed, specifically by using kasturi leaves, which are known to contain secondary metabolic compounds such as flavonoids, alkaloids, saponins, and tannins that can lower hyperlipidemia levels. This study aims to assess the effectiveness of ethanol extract from kasturi leaves (Mangifera casturi Kosterm) in reducing hyperlipidemia levels in white mice (Mus musculus). This research uses a pure experimental method. A total of 25 male white mice were induced with quail egg yolk. The treatments were divided into five groups: negative control (NA CMC), positive control (simvastatin), and three doses of ethanol extract from kasturi leaves (14 mg/20g BB, 28 mg/20g BB, and 56 mg/20g BB). Data analysis was performed using one-way ANOVA. The results of this study showed that the ethanol extract of the leavesThe results of this study indicate that the ethanol extract of kasturi leaves is effective in reducing hyperlipidemia levels in white mice, with a dosage of 56 mg/20g of body weight showing an effectiveness of 22.03%, and a decrease comparable to simvastatin 10 mg, which is a dose of 28 mg/20g of body weight.